The role of hydrazine in mixed fuels (H2O2/N2H4) for Au–Fe/Ni nanomotors1. Issue 87 (20th September 2015) - Xiao, Qing; Li, Ju; Han, Jing; Xu, Kai-Xuan; Huang, Zong-Xiong; Hu, Juan; Sun, Jian-Jun
<x xml:space="preserve">Abstract</x> Hydrazine in mixed fuels facilitates the oxidation of H2O2 to oxygen bubbles that propel the Au–Fe/Ni nanomotors.